Interrelation of the Estimation of Social and Economic Development of the Region and Quality of Water Resources - Matveeva, L.G.; Kosolapova, N.A.; Nikitaeva, A.Y.; Likhatskaya, E.A. (Journal of Environmental Science and Engineering Technology, 2019)
The paper validates the practicability of studying the problem of the quality of water at a regional level taking into account the mutual interaction between soci?-economic and hydroeconomic systems of the territories. The research revealed the limitations of the existing methods of estimation of the quality of water in the light of creation of informational and analytical basis of making managerial decisions. Accordingly, the authors suggest using the analytical tools of fuzzy logic, cluster analysis and neural networks to build an integral estimation of degree of water pollution and to classify water bodies according to the degree of their pollution and similarity of conditions and parameters of pollution. On the basis of the data concerning the quality of water resources in the river basin neural network was built, allowing to determine clusters of regions according to the quality of water resources. As input variables we used the information on the volume of drawing and dropping of water for each region, the amount of wastewater, which is polluted. The suggested methods allow greatly increase the opportunities to make managerial decisions with the help of interrelated estimation of the quality of water resources and the indicators of social and economic development of regional economic systems.